Pengembangan Konsep Digital Service Pada Badan Usaha Milik Desa Kabupaten OKU Timur - Pamuji Muhammad Jakak; Darius Antoni; Muhamad Akbar (Jurnal Informatika Global)
Information and communication technology (ICT) is currently developing rapidly. This can be seen from the utilization and use of ICT can not be separated from all activities of the organization or company. With the use of ICT, the Government through the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration invites local governments to jointly build Village Owned Enterprises (BUMDES). The establishment of BUMDES as one of the social institutions that favors the interests of the community through its contribution to services. This study aims to develop BUMDES digital services to improve services to the community. This research was conducted in the province of South Sumatra, precisely in the district. East OKU which consists of 20 sub-districts, 305 definitive villages, 7 sub-districts, and 20 preparatory villages. Village-Owned Enterprises (BUMDes), have two business units and one priority business unit. The types of businesses that exist in BUMDes can be clustered into several parts, namely: agriculture and farming engaged in (plantation and agriculture), banking is engaged in (savings and loans/capital), brokering is engaged in services (intermediaries), Holding is engaged in ( village potential), livestock and fishing is engaged in (livestock and fishery), renting is engaged in (rent/loan), serving is engaged in (services), trading is engaged in (trade). This research method uses qualitative, by conducting observations, interviews, and documentation. So that a digital service development is needed to facilitate community business activities in East OKU through the Village-Owned Enterprises (BUMDes) of East OKU.Keywords : ICT, Bumdes, OKU Timur, Digital Services, e-government